Residual effect of rock-phosphate and PSB on rice yield and soil properties - BISWAS, SIDDHARTHA SANKAR; BISWAS, DIPAK RANJAN; PURAKAYASTHA, TAPAN JYOTI; SARKAR, ABHIJIT; KUMAR, RAJESH; DAS, TAPAS KUMAR; BARMAN, MANDIRA; PABBI, SUNIL; GHOSH, AVIJIT; PAL, RAM (The Indian Journal of Agricultural Sciences, 2025)
Use efficiency of direct application of phosphorus (P) hardly exceeds 15-20% because of fixation to soils. The fixed-P could be utilized subsequently if it is brought to plant usable form. An experiment was conducted at Division of Soil Science and Agricultural Chemistry, ICAR-Indian Agricultural Research Institute, New Delhi during 2017-18 to investigate the residual effects of different P sources like di-ammonium phosphate (DAP), rock phosphate (RP), RP+ phosphorus solubilizing bacteria (PSB) and DAP+RP+PSB on rice yield, P uptake, P dynamics and enzyme activities in an Inceptisol. Results indicated that application of DAP30+RP60+PSB had 20.7, 24.3,19.6, 21.0, 28.1, 33, 15.2, 14.4 and 29.4% higher rice grain and straw yields, grain and straw P uptakes, available and saloid P, dehydrogenase, acid phosphatase and alkaline phosphatase activities respectively, as compared to DAP treatment. Thus, it can be inferred that application of DAP+RP+PSB can reduce fertilizer P consumption by 50%, and support the residual (second) crop better than conventional P-fertilizers, and improve soil available and saloid P status as well as enzymatic activities.